New, long-acting form of nifedipine: efficacy and safety in patients with mild to moderate arterial hypertension - E. V. Alimova; S. Yu. Martsevich; V. M. Gorbunov; A. D. Deev; V. N. Khirmanov; L. A. Sokolova; V. I. Podzolkov; Yu. A. Karpov (Российский кардиологический журнал)
The aim of the study was to compare efficacy and safety of a new, prolonged-action nifedipine form - nifecard-XL, and standard nifedipine tablets, in arterial hypertension (AH). One hundred forty-seven individuals with mild to moderate AH (61 males, 86 females), aged 21-81, were included. In a randomized, cross-over study, patients were consecutively administered nifecard-XL (30 mg once a day), or corinfar (10 mg 3 times a day), for one month each. In non-responders, the dose was doubled after 2 weeks. Before 1st and 2nd course, there were control one-week periods, with all antihypertensives withdrawn. Efficacy was assessed during blood pressure (BP) office measurements and 24-hour BP monitoring. Total number of persons who completed the trial was 127. Nifecard-XL (30 mg per day) was effective in 108 articipants, and in another 29 daily dose of 60 mg was needed. Corinfar (30 mg a day) was effective in 93 patients, and another 41 individuals had to be administered 60 mg. Mean daily dose for nifecard-XL was 36.4+12.3 mg, for corinfar - 39.2+13.9 mg. According to office BP levels, nifecard-XL significantly better lowered systolic BP than corinfar. Both agents were equal in reducing diastolic BP. During 24-hour BP monitoring, nifecard-XL and corinfar significantly decreased systolic, diastolic, and mean BP, temporal indexes of systolic and diastolic BP, without any substantial differences between both agents. Adverse events were typical for this class of antihypertensives, with 33 events registered in corinfar group, and 16 - in nifecard-XL group.